2016
DOI: 10.1098/rsif.2016.0030
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making without a brain: how an amoeboid organism solves the two-armed bandit

Abstract: Several recent studies hint at shared patterns in decision-making between taxonomically distant organisms, yet few studies demonstrate and dissect mechanisms of decision-making in simpler organisms. We examine decision-making in the unicellular slime mould Physarum polycephalum using a classical decision problem adapted from human and animal decision-making studies: the two-armed bandit problem. This problem has previously only been used to study organisms with brains, yet here we demonstrate that a brainless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 44 publications
1
78
0
Order By: Relevance
“…This outcome is usually referred to as maximizing (e.g., deVilliers, 1977). Similar results have been reported for great tits (Krebs, Kacelnik, & Taylor, 1978), threespined sticklebacks (Thomas, Kacelnik, & Van Der Meulen, 1985), bumblebees (Keasar, Rashkovich, Cohen, & Shmida, 2002), and individual slime mold cells (Reid et al, 2016) working in environments analogous to concurrent ratio schedules with unequal ratios in the components. To describe this outcome as maximizing implies that a mechanism different from the proportional mechanism implied by matching (Eq.…”
supporting
confidence: 83%
“…This outcome is usually referred to as maximizing (e.g., deVilliers, 1977). Similar results have been reported for great tits (Krebs, Kacelnik, & Taylor, 1978), threespined sticklebacks (Thomas, Kacelnik, & Van Der Meulen, 1985), bumblebees (Keasar, Rashkovich, Cohen, & Shmida, 2002), and individual slime mold cells (Reid et al, 2016) working in environments analogous to concurrent ratio schedules with unequal ratios in the components. To describe this outcome as maximizing implies that a mechanism different from the proportional mechanism implied by matching (Eq.…”
supporting
confidence: 83%
“…Second, many natural and artificial systems from amoebas (Reid et al, 2016) to humans (Moussaïd et al, 2010) need to implement their decision rules through local interaction rules, especially when the collectives have a decentralized structure. We will occasionally make reference to how some algorithms are implemented in distributed systems.…”
Section: Introductionmentioning
confidence: 99%
“…Ant colonies may be considered a singular brain, with each ant acting as a neuron-a suggestion made by Douglas Hofstadter [28] in 1980 and supported by cognitive scientists since. Studies of slime molds have suggested that neurons may not even be necessary for biological cognition [29]. If neurons are not necessary for cognition and collections of neurons can act collectively, then cognition is more broadly distributed than previously suggested-even within our own bodies.…”
Section: An Internet Of Processorsmentioning
confidence: 86%